An Inducible Cre-lox System to Analyze the Role of LLO in Listeria monocytogenes Pathogenesis - Brittney N. Nguyen; Daniel A. Portnoy (Toxins, 2020)
Listeriolysin O (LLO) is a pore-forming cytolysin that allows Listeria monocytogenes to escape from phagocytic vacuoles and enter the host cell cytosol. LLO is expressed continuously during infection, but it has been a challenge to evaluate the importance of LLO secreted in the host cell cytosol because deletion of the gene encoding LLO (hly) prevents localization of L. monocytogenes to the cytosol. Here, we describe a L. monocytogenes strain (hlyfl) in which hly is flanked by loxP sites and Cre recombinase is under the transcriptional control of the L. monocytogenes actA promoter, which is highly induced in the host cell cytosol. In less than 2 h after infection of bone marrow-derived macrophages (BMMs), bacteria were 100% non-hemolytic. hlyfl grew intracellularly to levels 10-fold greater than wildtype L. monocytogenes and was less cytotoxic. In an intravenous mouse model, 90% of bacteria were non-hemolytic within three hours in the spleen and eight hours in the liver. The loss of LLO led to a 2-log virulence defect in the spleen and a 4-log virulence defect in the liver compared to WT L. monocytogenes. Thus, the production of LLO in the cytosol has significant impact on the pathogenicity of L. monocytogenes.